The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1161/strokeaha.115.012248
|View full text |Cite|
|
Sign up to set email alerts
|

Heritability and Genome-Wide Association Analyses of Intracranial Carotid Artery Calcification

Abstract: ) that were significantly associated with ICAC volume. Rs1537372 replicated in an independent sample of 716 stroke patients (P combined =1.38×10 −10 ). Conclusions-ICAC volume is a heritable trait, which is partly explained by common genetic variation. We identified specific genetic variants associated with ICAC, which given the importance of ICAC in stroke risk, needs replication in larger-scale studies to further elucidate its genetic basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…Furthermore, none of them included both members of a pair. However, a previous study found 36% heritability of aortic arch calcification detected on nonenhanced CT scans [ 29 ]. This could have been due to the several differences between our study concepts such as the different imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, none of them included both members of a pair. However, a previous study found 36% heritability of aortic arch calcification detected on nonenhanced CT scans [ 29 ]. This could have been due to the several differences between our study concepts such as the different imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…candidate genes of inflammation, oxidative stress, growth factors, renin-angiotensin aldosterone system, and so-forth) has so far been demonstrated in several reports to affect the development of atherosclerosis [2]. Genetic variability in the candidate genes implicated in atherosclerosis may alter their transcriptional activity and contribute to susceptibility to cardiovascular disease [3][4][5][6][7][8][9][10][11]. In the pathogenesis of atherosclerosis genetic, environmental, and epigenetic factors are involved [4][5].…”
Section: Editorialmentioning
confidence: 99%
“…Genetic and epigenetic factors may be studied with two main approaches, candidate gene approach and genome wide association study (GWAS) approach [4][5][6][7][8][9]11]. Candidate gene approach is hypothesis-driven approach, whereas in GWAS approach appropriate subset of patients (i.e.…”
Section: Editorialmentioning
confidence: 99%
See 2 more Smart Citations